Implementasi Pembelajaran PPKn dalam Menanamkan Nilai Karakter Peserta Didik - Rizal, A Rizal; Burhan, Burhan; Irwandi, Irwandi; Nurwidyayanti, Nurwidyayanti (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
The purpose of this study was to determine PPKN learning strategies in instilling character values in students. This research was conducted at SMA Negeri 19 Bone in XI. Data collection techniques using the approach of observation, interviews, and documentation. This study uses a type of qualitative research. Data reduction was carried out then analyzed and verified using source triangulation. The results of this study indicate that, PPKN learning strategies in instilling character values in students are by identifying changes in students' behavior and personality, choosing an appropriate approach system in the learning process, choosing and establishing teaching and learning policies and techniques to guide teachers in carry out teaching activities, establish conditions for success as a benchmark for success standards so that they can be used as a guide for teachers to evaluate the results of teaching and learning activities. In conclusion, the implementation of Pancasila and Citizenship Education learning in instilling character values in students at SMAN 19 Bone, namely through the stages of learning in class, such as praying together before starting lessons, applying discipline by arriving on time, giving assignments and motivating students after learning is finished. Keywords: Character, Character Values Education, PPKN Learning.